Minimize the distribution cost of tortillas at Corner Kebab using the Stepping Stone method - Rini, Ratih Setyo; Vidada, Irwin Ananta; Istiatik, Dasih Irma; Rani, Rani; Saridawati, Saridawati (Jurnal Orientasi Bisnis dan Entrepreneurship (JOBS), 2024)
This research explores optimizing transportation costs for Corner Kebab, a kebab business, by employing the stepping stone method. It addresses operational expenses, encompassing factory and transportation costs, to enhance the delivery of kebab skin (tortilla). The study evaluates the distribution process from MiniFroz and Defroz factories in East Jakarta and Serpong to three Corner Kebab outlets in Pondok Benda, Cidodol South Jakarta, and Bukit Dago. By minimizing tortilla distribution costs, the stepping stone method identifies an optimal daily expense of Rp. 212,000,- for Corner Kebab, surpassing the Rp. 222,000,- incurred through the North West Coast Method. This approach offers cost-saving benefits for the company. Despite the well-established nature of transportation problems and optimization techniques, this research contributes novelty by applying the stepping stone method to the kebab industry, specifically analyzing tortilla delivery costs. This focus on a niche business context enhances understanding and provides valuable insights for operational cost reduction in similar enterprises.